Transformative Islamic Religious Education at The University of Indonesia: Implementation of The Deradicalization Curriculum as An Effort to Cultivate Religious Moderation - Nuha, Ulin; Muhammad Nur Hayid (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
One of the University of Indonesia policies in cultivating religious moderation in its students is the implementation of deradicalization curriculum. This research is very important because the results of this research can be used as a reference in efforts to eradicate extremism among students who, as we know, are prospective intellectuals and national leaders in the future. The aim of this research is to finding out to what extent the implementation of deradicalization curriculum in Islamic Religious Education at the University of Indonesia is able in cultivating religious moderation among it'snew Muslim students in 2023. By using descriptive research methods with a quantitative approach, the author found that the data analysis that the author carried out showed that correlation coefficient value (rxy) = 1. This correlation analysis showed that the correlation between deradicalization curriculum and religious moderation of Muslim students who have just entered the University of Indonesia in 2023 have a perfect relationship. Meanwhile, with an error level of 0.05 and a total of N=7.530, the x and y correlation significance test showed that tcalculated is 0.58 whereas ttable is 0.1966. Interpretation of this correlation significant test of these two variables showed that H0 is rejected and Ha is accepted, which means there is a significant relationship between deradicalization curriculum in Islamic Religious Education and religious moderation of Muslim students who have just entered the University of Indonesia in 2023. The implication of this research results is that the deradicalization curriculum in Islamic religious education that has been implemented by the University of Indonesia can be a guide for other similar universities in cultivating religious moderation among their students.